Data for Saccharina latissima RNA seq experiment ... - Dahle, Håkon (Dryad, 2025)
Sugar kelp (Saccharina latissima) is an ecologically and increasingly economically important kelp, distributed from temperate to Arctic rocky shores. However, S. latissima is presently threatened by ongoing climate changes. Genetic variations have previously been identified across S. latissima populations. However, little is known regarding the genetic basis for adaptation and acclimation to different environmental conditions. In this study, a common garden experiment was performed with sporophytes originating from North-Norway (NN), Mid-Norway (MN), and South-Norway (SN), representing areas with highly different temperatures and photoperiods. Transcriptomic analyses revealed significant variation in the gene expression of cultures from North-Norway, associated with low temperature and long photoperiods, compared to Mid- and South-Norway. Genes that were differentially expressed under different photoperiod and temperature conditions included genes linked to photosynthesis, chlorophyll biosynthesis, heat ... : A common garden experiment (CGE) was carried out between 2 February – 13 March 2018 at the University of Bergen, with material of S. latissima collected in North-Norway (69° 38’ N, 18° 57’ E) (NN), Mid-Norway (63° 43’ N, 8° 49’ E) (MN) and South-Norway (60° 16’ N, 5° 13’ E) (SN). Tissue pieces carrying mature sori with sporangia were cut from 10-12 Saccharina latissima, collected at 1-5 m depth between 8-12 January 2018 at all three sites in Norway. The material from NN and MN was wrapped up in moist paper with cooling elements and transported to the laboratory and seeded the day of arrival, during two successive days. The tissue with sori was treated as described in Forbord et al. (2018) to prevent diatom growth in the cultures, and thereafter submerged in beaker glasses with cool (12°C) sterile sea water and stirred until spore release was observed using microscope. The spore solution was applied to tagged, clean and heat-treated granite stones (10x10 cm). After 10 min exposure to spore solution the stones ...